Mechanical power of the sweeping leg during Osoto-gari - Imamura, R. T.; Iteya, M.; Mandeville, D.; Parker, D. L. (Association for the Scientific Studies on Judo, Kodokan, 2011)
The study provides a viable means to investigate the mechanical power generated by the osoto-gari sweep. Overall, the study reaffirms the common notion that more experienced judoka are able to execute osoto-gari faster and with more power than novice judoka. Ankle contribution continues to be a major difference between skill levels. While previous studies have alluded to the possibility of ankle power being a product of a kinetic link system, this study did not substantiate that notion. Rather, it is believed that the ankle not only contributes to overall sweeping power but also plays a role in placing the leg in an optimal sweeping position.